2021
DOI: 10.3390/ijerph182312728
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifications at the Center of the Barker Hypothesis and Their Transgenerational Implications

Abstract: Embryo/fetal nutrition and the environment in the reproductive tract influence the subsequent risk of developing adult diseases and disorders, as formulated in the Barker hypothesis. Metabolic syndrome, obesity, heart disease, and hypertension in adulthood have all been linked to unwanted epigenetic programing in embryos and fetuses. Multiple studies support the conclusion that environmental challenges, such as a maternal low-protein diet, can change one-carbon amino acid metabolism and, thus, alter histone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…It is well established that developmental programming operates via epigenetic changes in chromatin architecture, DNA methylation, microRNA expression, histone modifications, and others [ 138 , 139 , 140 , 141 , 142 , 143 ]. We hypothesized that somatic polyploidy can be one of the epigenetic mechanisms of developmental programming in slowly renewing and terminally differentiated organs.…”
Section: Polyploidy Meets the Hallmarks Of Developmental Programming ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that developmental programming operates via epigenetic changes in chromatin architecture, DNA methylation, microRNA expression, histone modifications, and others [ 138 , 139 , 140 , 141 , 142 , 143 ]. We hypothesized that somatic polyploidy can be one of the epigenetic mechanisms of developmental programming in slowly renewing and terminally differentiated organs.…”
Section: Polyploidy Meets the Hallmarks Of Developmental Programming ...mentioning
confidence: 99%
“…We hypothesized that somatic polyploidy can be one of the epigenetic mechanisms of developmental programming in slowly renewing and terminally differentiated organs. This suggestion is based on the similarity between the properties of polyploidy and the mechanisms of developmental programming described in the literature [ 131 , 132 , 140 , 141 , 144 ].…”
Section: Polyploidy Meets the Hallmarks Of Developmental Programming ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, epigenetic alterations highlight these adverse disease outcomes. Due to environmental or maternal lifestyle factors, these modifications have been shown to significantly induce offspring metabolic syndrome, obesity, heart disease, and hypertension ( Ryznar et al, 2021 ). An accumulation of data has demonstrated that prenatal cadmium exposure induces many epigenetic alterations, such as DNA methylation and post-translational histone modifications, as well as influences on differential micro-RNA expression within the developing offspring ( Vilahur et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic changes determine modifications in the gene expression and, consequently, in the metabolic programming of the fetus, predisposing it to the onset of metabolic diseases later in life. It has been observed that the early stages of embryo development represent a time window in which cells are most susceptible to epigenetic changes [ 21 ]. However, despite the fact that the first trimester represents a crucial period in the metabolic programming of the fetus, it is also true that fetal exposure to unfavorable intra-uterine conditions continues to influence epigenetic modifications in the next stages of development.…”
Section: Introductionmentioning
confidence: 99%